The Influence of Income, Gold Prices and Inflation on Rahn PT's Financing Distribution. Pawnshop with ROA as an Intervening Variable - Ahmat Alfian Wardana; Kurniawati Meylianingrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The sharia financial sector, especially sharia pawnshops, is very interesting to study because of its strategic role in an economy based on Islamic principles. In this context, variables such as inflation, gold prices and pawnshop income greatly influence the operations and financial performance of Islamic financial institutions. Quantitative research is used to investigate how pawnshop income, gold prices and inflation rates influence the distribution of rahn financing. The aim of this research is to look at the influence of pawnshop income, gold prices and inflation rates on the distribution of rahn financing as well as the indirect influence through ROA at sharia pawnshops in Indonesia for the 2018-2022 period. This research analyzes all sharia pawnshop financial reports in Indonesia from 2018 to 2022, with 60 samples. The data analysis method used is path analysis using the Windows Eviews12 program. The research results show that pawnshop income, gold prices, inflation have no effect on ROA. Pawnshop income, inflation, ROA have no effect on rahn distribution. Gold prices influence rahn distribution. Pawnshop income, gold prices, inflation do not have a significant effect on the distribution of rahn financing through ROA, or ROA cannot mediate the influence of pawnshop income on the distribution of rahn financing in the 2018-2022 period.